2021
DOI: 10.1007/s10856-021-06499-6
|View full text |Cite
|
Sign up to set email alerts
|

SDF-1α gene-activated collagen scaffold enhances provasculogenic response in a coculture of human endothelial cells with human adipose-derived stromal cells

Abstract: Novel biomaterials can be used to provide a better environment for cross talk between vessel forming endothelial cells and wound healing instructor stem cells for tissue regeneration. This study seeks to investigate if a collagen scaffold containing a proangiogenic gene encoding for the chemokine stromal-derived factor-1 alpha (SDF-1α GAS) could be used to enhance functional responses in a coculture of human umbilical vein endothelial cells (HUVECs) and human adipose-derived stem/stromal cells (ADSCs). Functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…CXCL12 is a chemokine known for its potent stem cell homing abilities, and application of both this chemokine and mimetics have been shown previously to stimulate wound healing (Badillo et al, 2007;Xu et al, 2022a). Another group integrated CXCL12 into their GAG therapeutic by using a hybrid polyethyleneimine (PEI)-CXCL12 containing collagen-chondroitin sulfate scaffold (Laiva et al, 2021).…”
Section: Glycosaminoglycansmentioning
confidence: 99%
“…CXCL12 is a chemokine known for its potent stem cell homing abilities, and application of both this chemokine and mimetics have been shown previously to stimulate wound healing (Badillo et al, 2007;Xu et al, 2022a). Another group integrated CXCL12 into their GAG therapeutic by using a hybrid polyethyleneimine (PEI)-CXCL12 containing collagen-chondroitin sulfate scaffold (Laiva et al, 2021).…”
Section: Glycosaminoglycansmentioning
confidence: 99%
“…The lymphangiogenic function increases with infiltrating macrophages that produce (VEGF-C) [35]. In addition to lymphangiogenesis, VEGF-C may regulate physiological angiogenesis [35,36]. Studies have also shown that SIM can suppress the growth of bacterial pathogens [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…These charged nanoparticles are then soak-loaded into our coll-CS scaffold to generate the gene-activated scaffolds. Our previous studies have also shown that the PEI-based gene-activated scaffold can cause transient overexpression of the therapeutic transgene in a range of wound-healing cells and promote their regenerative abilities [21,24,25]. Traditionally, the gene-activated scaffold was developed to target host cells and promote local repair [26].…”
Section: Introductionmentioning
confidence: 99%